Divergent functional outcomes of NLRP3 blockade downstream of multi-inflammasome activation: therapeutic implications for ALS - Clénet, Marie-Laure; Keaney, James; Gillet, Gaëlle; Valadas, Jorge S.; Langlois, Julie; Cardenas, Alvaro; Gasser, Julien; Kadiu, Irena (Frontiers in Immunology, 2023)
NOD-Like Receptor Family Pyrin Domain Containing (NLRP3) inflammasome modulation has emerged as a potential therapeutic approach targeting inflammation amplified by pyroptotic innate immune cell death. In disease characterized by non-cell autonomous neurodegeneration including amyotrophic lateral sclerosis (ALS), activation of NLRP3 but also other inflammasome pathways including NLR family CARD domain-containing protein 4 (NLRC4) and non-canonical inflammasomes has been reported. Since functional redundancy can exist among inflammasome pathways, here we investigate the effects of NLRP3 inhibition on NLRP3, NLRC4 and non-canonical pathways to understand whether NLRP3 blockade alone can mitigate pro-inflammatory cytokine release and pyroptotic cells death in contexts where single or multiple inflammasome pathways independent of NLRP3 are activated. In this study we do not limit our insights into inflammasome biology by solely relying on the THP1 monocytic line under the LPS/nigericin-mediated NLRP3 pathway induction paradigm. On the contrary, we dig deeper into the inflammasome biology in cells lines expressing gain of function (GoF) mutations in multiple inflammasomes, primary human monocytes, macrophages, healthy and patient (ALS)-iPSC derived microglia stimulated for both canonical and non-canonical inflammasome activation pathway, to acquire comprehensive biological insights on the therapeutic potential and limitations of NLRP3 inhibition in human in vitro systems displaying multi-inflammasome activation biology. We demonstrate that NLRP3 inhibition can modulate the function of NLRC4 and non-canonical inflammasome pathways but that these effects differ between immortalized, human primary innate immune cells, and iPSC-derived microglia. We test our hypothesis in more complex in vivo systems characterized by activation of multiple inflammasomes such as the SOD1 G93A mouse model. Through deep immune phenotyping by singlecell mass cytometry we discovered that acute NLRP3 inhibition does not ameliorate spinal cord 3 inflammation in this model. Taken together, our data suggests that NLRP3 inhibition alone may not be sufficient to address dynamic and complex neuroinflammatory pathobiological mechanisms including dysregulation of multiple inflammasome pathways in neurodegenerative disease such as ALS.